2018
DOI: 10.3390/catal8090351
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Supported Ionic Liquid Catalysts for the Hydrochlorination of Acetylene

Abstract: An efficient and stable heterogeneous Zeolite Supported Ionic Liquid Catalyst (IL/CaX) has been explored in acetylene hydrochlorination reaction. The IL/CaX catalyst exhibits excellent space time yields of vinyl chloride (VCM), when compared to the benchmark of Au/C systems. Through characterization and kinetic studies, the reaction follows a two-site mechanism, which is described as the adsorbed hydrogen chloride on the Ca2+ in zeolite, reacting with the adsorbed acetylene on the cation of ionic liquid to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…As showed in Figure b, the activation energy ( E a ) of Au/N, S‐AC‐700 and Au/AC were 48 and 72 kJ/mol , respectively. The large difference between activation energy of Au/N, S‐AC‐700 and Au/AC catalysts implied that the active cationic gold in the catalysts may have distinct electronic environment or the reactions employing different catalysts may occur via different mechanisms ,,. Catalytic performance of Au/N, S‐AC‐700 catalyst was also highly dependent on the HCl/C 2 H 2 ratio (Figure S).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As showed in Figure b, the activation energy ( E a ) of Au/N, S‐AC‐700 and Au/AC were 48 and 72 kJ/mol , respectively. The large difference between activation energy of Au/N, S‐AC‐700 and Au/AC catalysts implied that the active cationic gold in the catalysts may have distinct electronic environment or the reactions employing different catalysts may occur via different mechanisms ,,. Catalytic performance of Au/N, S‐AC‐700 catalyst was also highly dependent on the HCl/C 2 H 2 ratio (Figure S).…”
Section: Resultsmentioning
confidence: 99%
“…However, AuCl 3 is a good electron acceptor which is willing to take one Cl − ion from HCl, therefore, sufficient supply of HCl can effectively improve the catalytic performance of Au/N, S‐AC‐700 catalyst (Figure ). Furthermore, the adsorption HCl on the active Au 3+ could further activate the adsorbed C 2 H 2 , leading to a decrease in the activation energy of the reaction (Figure b) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the selection of non-mercury catalysts poses a signicant challenge, a number of catalytic formulations have been proposed including noble metal chlorides, non-noble metal chlorides [30][31][32][33][34][35] and even non-metallic materials. [36][37][38][39][40][41][42][43][44] Among them, Pd catalysts have been considered to be very effective for the hydrochlorination of acetylene. For example, Hutchings et al explored the catalytic performance of carbon supported with a series of metal chlorides and found that the conversion of acetylene to VCM decreased in the following order: Pd(II) > Hg(II) > Cu(II) $ Cu(I) > Ag(I) > Cd(II) > Zn(II).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, gold-based catalysts are good candidates for commercial success using this approach [1,3], since the reaction conditions are mild for Au and also present comparable catalytic properties to Hg. However, there is still an ongoing research investigating alternative activity catalysts to synthesize VCM by acetylene hydrochlorination approach [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%